Pengembangan Kualitas Pribadi Konselor Secara Profesional dalam Pelayanan Bimbingan Konseling - Insani, Nurul; Astuti, Budi (Universitas PGRI Kanjuruhan Malang, 2024)
The personal qualities of a counselor are crucial in the implementation of guidance and counseling. A counselor must demonstrate themselves as a whole and authentic individual, capable of building unique, harmonious, dynamic, persuasive, and creative interpersonal relationships. These qualities serve as the driving force behind the success of counseling services. The purpose of this study is to describe the Development of Counselor's Personal Qualities Professionally in Counseling Services. The findings of this research indicate that a counselor's personal qualities encompass not only individual aspects such as empathy, patience, and integrity but also contextual factors like culture, religious values, and professionalism within the counseling practice context